2016
DOI: 10.1038/srep32418
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Simulated Microgravity on Cytoskeleton and Viscoelastic Properties of Endothelial Cell

Abstract: This study focused on the effects of simulated microgravity (s-μg) on mechanical properties, major cytoskeleton biopolymers, and morphology of endothelial cells (ECs). The structural and functional integrity of ECs are vital to regulate vascular homeostasis and prevent atherosclerosis. Furthermore, these highly gravity sensitive cells play a key role in pathogenesis of many diseases. In this research, impacts of s-μg on mechanical behavior of human umbilical vein endothelial cells were investigated by utilizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 59 publications
2
47
2
1
Order By: Relevance
“…Our data demonstrate that space microgravity suppress energy metabolism, cytokine secretion and ECM expression, modulate distinctly adhesive molecule expression, induce cytoskeletal remodeling, and enhance exosome-mediated mRNA transfer ( Figure 11 ). Our results conformed several major findings demonstrated by those studies on ECs in microgravity effect simulation using clinostats, such as decreased cell-surface expression of ICAM-1 and VCAM-1 ( Grimm et al, 2010 ; Grenon et al, 2013 ), reduced release of pro-inflammatory cytokines ( Cotrupi et al, 2005 ; Grimm et al, 2010 ; Griffoni et al, 2011 ; Grenon et al, 2013 ) and disorganization of F-actin and microtubules ( Kang et al, 2011 ; Janmaleki et al, 2016 ). However, unlike the effect of simulated microgravity, space microgravity neither enhanced NO production nor induced 3D growth in the current work, indicating a different role in angiogenesis between the two approaches.…”
Section: Discussionsupporting
confidence: 91%
“…Our data demonstrate that space microgravity suppress energy metabolism, cytokine secretion and ECM expression, modulate distinctly adhesive molecule expression, induce cytoskeletal remodeling, and enhance exosome-mediated mRNA transfer ( Figure 11 ). Our results conformed several major findings demonstrated by those studies on ECs in microgravity effect simulation using clinostats, such as decreased cell-surface expression of ICAM-1 and VCAM-1 ( Grimm et al, 2010 ; Grenon et al, 2013 ), reduced release of pro-inflammatory cytokines ( Cotrupi et al, 2005 ; Grimm et al, 2010 ; Griffoni et al, 2011 ; Grenon et al, 2013 ) and disorganization of F-actin and microtubules ( Kang et al, 2011 ; Janmaleki et al, 2016 ). However, unlike the effect of simulated microgravity, space microgravity neither enhanced NO production nor induced 3D growth in the current work, indicating a different role in angiogenesis between the two approaches.…”
Section: Discussionsupporting
confidence: 91%
“…Fundamental work carried out by Tabony, Pochon, and Papaseit showed that while tubulin self-assembly into microtubules occurs independent of gravity, the assembly and organization of the microtubule network is gravity dependent (Papaseit et al, 2000;Tabony et al, 2002). Importantly, this gravity-dependent organization of the microtubule network has since been described in multiple cell lines during both real and simulated microgravity exposures (Vassy et al, 2001;Uva et al, 2002;Hughes-Fulford, 2003;Rosner et al, 2006;Janmaleki et al, 2016) and possibly be the result of a poorly defined microtubule organizing center (MTOC) (Lewis et al, 1998). Taken together these data highlight an important regulatory role for the microtubule network and the MTOC following exposure to a microgravity environment.…”
Section: The Impact Of Microgravity Of Cell Cytoskeletonmentioning
confidence: 99%
“…It should be noted that similar changes were observed in mammalian cells under conditions of SMG. Human endothelial cells incubated under conditions of SMG exhibited a round cell shape with actin disorganization (Janmaleki, Pachenari, Seyedpour, Shahghadami, & Sanati‐Nezhad, ). Comparative biology of microtubule‐associated genes also revealed remarkable evolutionary coincidence.…”
Section: Discussionmentioning
confidence: 99%